Comparative Effectiveness of Osseous Resective Surgery with Apically Repositioned Flap: Supracrestal Fiber Retention vs. Conventional Technique—A Systematic Review and Meta-Analysis - Karishma Nitin Lodaya; Vineet Kini (Journal of the California Dental Association, 2025)
Introduction Evidence based research suggests apically positioned flap with osseous resective surgery tends to be superior in terms of clinical outcomes to any other flap design to treat periodontal pockets along with underlying osseous defects where regenerative osseous surgery is not indicated. Slowly fiber retention osseous resective surgery (FRORS) has gained popularity as it is minimally invasive and retains the supracrestal component along with better clinical outcomes. Hence, this SRMA aimed to compare clinical results of ORS with apically positioned flap and FRORS with apically positioned flap.Objective The objective of this systematic review and meta-analysis is to measure the change in Probing pocket depth, change in Clinical attachment levels and change in Gingival recession post- surgery.Methodology The protocol of this review was registered in PROSPERO (CRD42023473337). The review was conducted according to PRISMA 2020 guidelines, using ROB tool.Results and Conclusion This systematic review and meta-analysis suggest that supra-crestal fiber retention osseous resective surgery with apically positioned flap is equally effective as osseous resective surgery with apically positioned flap in elimination of pocket depths, maintaining clinical attachment levels, less resection of the bone and restoring positive osseous architecture for maintenance.